2022
DOI: 10.3389/fonc.2022.869764
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Postoperative Tumor Burden on Patients With Brain Metastases

Abstract: BackgroundBrain metastases were considered to be well-defined lesions, but recent research points to infiltrating behavior. Impact of postoperative residual tumor burden (RTB) and extent of resection are still not defined enough.Patients and MethodsAdult patients with surgery of brain metastases between April 2007 and January 2020 were analyzed. Early postoperative MRI (<72 h) was used to segment RTB. Survival analysis was performed and cutoff values for RTB were revealed. Separate (subgroup) analyses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…This study shows that maximal EOR is critical for good long-term outcomes in older patients with BMs, as RTB = 0 significantly improves OS and local tumor control regardless of the cancer type. This finding is in accordance with recent investigations regarding the impact of RTB in younger patients (≤ 65 years) with brain metastases, which have proven low RTB to be a significant predictor for prolonged OS ( 23 ). Furthermore, it has been argued that maximal cytoreduction should be achieved, independent of the postoperative radiotherapy type ( 23 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study shows that maximal EOR is critical for good long-term outcomes in older patients with BMs, as RTB = 0 significantly improves OS and local tumor control regardless of the cancer type. This finding is in accordance with recent investigations regarding the impact of RTB in younger patients (≤ 65 years) with brain metastases, which have proven low RTB to be a significant predictor for prolonged OS ( 23 ). Furthermore, it has been argued that maximal cytoreduction should be achieved, independent of the postoperative radiotherapy type ( 23 ).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with recent investigations regarding the impact of RTB in younger patients (≤ 65 years) with brain metastases, which have proven low RTB to be a significant predictor for prolonged OS ( 23 ). Furthermore, it has been argued that maximal cytoreduction should be achieved, independent of the postoperative radiotherapy type ( 23 ). Postoperative MRI should confirm EOR, as intraoperative estimates can misjudge complete resection.…”
Section: Discussionsupporting
confidence: 93%
“…Especially, small and asymptomatic BMs are amenable to stereotactic radiosurgery (SRS), but large or symptomatic lesions require microsurgical resection for enduring symptom relief [9,10]. It has been shown that maximal tumor resection improves survival [11]. However, the local recurrence rate after resection is up to 50%, secondary to remnant tumor cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, changes in the molecular profile of the primary tumor established another important role of surgical resection in obtaining histopathological samples for further analysis (36). Maximal cytoreduction is an independent prognostic factor in the treatment of BM (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%